2020
DOI: 10.1099/acmi.0.000075
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity, circulation patterns and co-detections among rhinoviruses in Queensland, 2001

Abstract: Purpose Rhinoviruses (RVs) occur more frequently than other viruses and more often in people displaying symptoms than in those without. We sought to estimate the spectrum of RV diversity, RV species seasonality and to analyse RV involvement in respiratory virus co-detections. Methodology A convenience collection of 1179 airway sample extracts from patients with suspected respiratory infections, collected during 2001, was subjected to comprehensive molecular testing. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…While we excluded specimens isolated from outbreaks or for surveillance and samples from 2009 and 2016–2017 when testing patterns were obviously altered, we cannot be certain we controlled completely for this unknown. Type/subtype data for other viruses may have also improved the resolution of our findings, as other studies have noted variances in the timing of epidemics caused by different types of parainfluenza virus [ 4 , 6 ] and rhinovirus [ 21 ] and there is scant information available for RSV. Additionally, our study sample was drawn from patients ill enough to seek healthcare.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…While we excluded specimens isolated from outbreaks or for surveillance and samples from 2009 and 2016–2017 when testing patterns were obviously altered, we cannot be certain we controlled completely for this unknown. Type/subtype data for other viruses may have also improved the resolution of our findings, as other studies have noted variances in the timing of epidemics caused by different types of parainfluenza virus [ 4 , 6 ] and rhinovirus [ 21 ] and there is scant information available for RSV. Additionally, our study sample was drawn from patients ill enough to seek healthcare.…”
Section: Discussionmentioning
confidence: 75%
“…Despite this apparent interference, viral co-infections do occur, albeit with insufficient frequency to maintain an epidemic-level spread of the co-infecting viruses. A recent study reported infrequent co-detection of rhinovirus with other viruses [ 21 ], despite observations that rhinovirus continues to be shed for several weeks post-resolution of symptoms [ 22 ]. Negative associations have also been observed between the detection of influenza A, RSV, parainfluenza virus or coronavirus and co-detection of other respiratory viruses [ 8 , 23 , 24 ], providing further evidence for a refractory period after initial infection during which the host is less likely to be infected by subsequent exposure to another respiratory virus.…”
Section: Introductionmentioning
confidence: 99%
“…Although our study was limited to adults aged 21 years or older, the low co-detection rates we observed for rhinovirus and IAV in this population are strikingly similar to results from different patient populations, including a study of 2121 paediatric samples from the 2009 H1N1 IAV pandemic in France; 1247 samples from children who were symptomatic in Australia from 2003; 33 652 samples from patients of all ages in Australia over 12 years; and 44 230 samples from patients of all ages in Scotland collected over 9 years. 3,[8][9][10] Nickbash and colleagues also presented a mathematical model further supporting viral interference. 10 The similarities in results across different geographies, populations, and study designs support the idea that low virus co-detection rates have a biological basis rather than representing a confounder in a particular patient group.…”
Section: Discussionmentioning
confidence: 95%
“…[2][3][4] Since 2009, analyses of co-detections of common respiratory viruses, including rhinovirus and IAV or rhinovirus and respiratory syncytial virus (RSV), have shown that co-detections are significantly lower than would be expected by chance alone, also supporting the viral interference hypothesis. 3,[5][6][7][8][9][10] Another important observation was made in a small study of the live attenuated intranasal influenza vaccine, in which investigators observed decreased replication of the influenza vaccine strain in children who tested positive for another respiratory virus at the time of vaccine exposure. 11 In a mouse model, previous rhinovirus exposure attenuated IAV infection, with the caveat that rhinovirus does not replicate in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a respiratory virus pandemic can affect circulation, age distribution, and other properties of seasonal RVI (Meningher et al, 2014;Navarro-Marí et al, 2012), and several studies have provided evidence of respiratory virus interactions during circulation (Ånestad, 1987;Arden et al, 2020;Casalegno et al, 2010;Nickbakhsh et al, 2019;Wu et al, 2020). Our study demonstrates the impact of the SARS-CoV-2 infection pandemic on the prevalence of other RVI and age distribution of children hospitalized with ARIs, as well as presents clinical features of COVID-19 in children in Moscow, Russia during the autumn wave of the COVID-19 pandemic in 2020 (Fig.…”
Section: Discussionmentioning
confidence: 99%